2005
DOI: 10.1159/000085556
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Multiple Sclerosis in Kuwait: New Trends in Incidence and Prevalence

Abstract: The epidemiology of multiple sclerosis (MS) is undergoing dramatic changes; MS is occurring with increased frequency in many parts of the world. In this retrospective study, we examined the changes in incidence and prevalence of MS in Kuwait in the period between 1993 and 2000. We analyzed the records of patients with clinically defined and laboratory supported MS. The total incidence rate increased from 1.05/100,000 population in 1993 to 2.62/100,000 in 2000. The increased incidence of MS was most pronounced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 35 publications
6
77
3
1
Order By: Relevance
“…However, it has been suggested that stress could produce cerebrovascular alterations which might be etiologically related to plaque formation [26], or such patients could develop MS in the context of protracted emotional arousal including anger [27,28]. Alternatively, environmental pollution, exposure to toxins and chemicals as a result of the Iraqi occupation might be associated with an increased MS risk in our target population as suggested earlier [7,29]. …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, it has been suggested that stress could produce cerebrovascular alterations which might be etiologically related to plaque formation [26], or such patients could develop MS in the context of protracted emotional arousal including anger [27,28]. Alternatively, environmental pollution, exposure to toxins and chemicals as a result of the Iraqi occupation might be associated with an increased MS risk in our target population as suggested earlier [7,29]. …”
Section: Discussionmentioning
confidence: 76%
“…In Kuwait, MS is also more common in females and displays a much higher prevalence among Kuwaitis (31.2/100,000) than non-Kuwaitis (5.6/100,000) [10]. Furthermore, Kuwait has experienced an increase in the incidence of MS (from 1.1/100,000 population in 1993 to 2.6/100,000 in 2000) and in the prevalence of MS (from 6.7/100,000 in 1993 to 14.8/100,000 in 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there have been an increasing prevalence and incidence of MS over the past few decades in this region [42,43]. Within the country of Kuwait, there has been a twofold increase in both the prevalence and incidence of MS between 1993 and 2000 [44]. Some of this increase can be attributed to better ascertainment with the availability of MRI imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it could be real increase in MS risk in our setting due to the increasing magnitude of specific environmental factors and/or adaptation of dietary and lifestyles patterns precipitating MS risk. Kuwait has moved from a low to a moderately high-risk setting for MS and aforementioned factors have been implicated for this steady increase of MS risk in Kuwait [12, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Majority of the migrants are men with a low educational attainment [9-11]. Among nationals, the male and female literacy rates (defined as individuals aged 10 years or more and who can read and write) are 98.5 and 91.2%, respectively, with a gender ratio (male: female) of 1.04 at birth [12]. Petroleum and petrochemical products constitute the major industry.…”
Section: Methodsmentioning
confidence: 99%